Parkinson's disease age at onset genome‐wide association study: Defining heritability, genetic loci, and α‐synuclein mechanisms - Blauwendraat, Cornelis; Heilbron, Karl; Vallerga, Costanza L.; Bandres‐Ciga, Sara; von Coelln, Rainer; Pihlstrøm, Lasse; Simón‐Sánchez, Javier; Schulte, Claudia; Sharma, Manu; Krohn, Lynne; Siitonen, Ari; Iwaki, Hirotaka; et al. (Movement disorders, 2019)
Background Increasing evidence supports an extensive and complex genetic contribution to PD. Previous genome‐wide association studies (GWAS) have shed light on the genetic basis of risk for this disease. However, the genetic determinants of PD age at onset are largely unknown. Objectives To identify the genetic determinants of PD age at onset. Methods Using genetic data of 28,568 PD cases, we performed a genome‐wide association study based on PD age at onset. Results We estimated that the heritability of PD age at onset attributed to common genetic variation was ∼0.11, lower than the overall heritability of risk for PD (∼0.27), likely, in part, because of the subjective nature of this measure. We found two genome‐wide significant association signals, one at SNCA and the other a protein‐coding variant in TMEM175, both of which are known PD risk loci and a Bonferroni‐corrected significant effect at other known PD risk loci, GBA, INPP5F/BAG3, FAM47E/SCARB2, and MCCC1. Notably, SNCA, TMEM175, SCARB2, BAG3, and GBA have all been shown to be implicated in α‐synuclein aggregation pathways. Remarkably, other well‐established PD risk loci, such as GCH1 and MAPT, did not show a significant effect on age at onset of PD. Conclusions Overall, we have performed the largest age at onset of PD genome‐wide association studies to date, and our results show that not all PD risk loci influence age at onset with significant differences between risk alleles for age at onset. This provides a compelling picture, both within the context of functional characterization of disease‐linked genetic variability and in defining differences between risk alleles for age at onset, or frank risk for disease. © 2019 International Parkinson and Movement Disorder Society